Air pollution in Kurdistan Region of Iraq: A review - Zanist Hama-Aziz (Program Pascasarjana Universitas Sriwijaya, 2021)
Air pollution is an increasingly environmental problem worldwide. People from Iraq and the Kurdistan Region of Iraq (KRI) constantly complain of poor air quality in the region. Many studies have investigated particular aspects of air pollution in theKRI, the issue, however, has never been comprehensively discussed. This study, unlike its precedents, collects all the documents, research articles, and ground facts available concerning air pollution, and aims to thoroughly understand all dimensions of the issue and classifies its significant factors and sources. The result revealed that, compared to 40 years ago, current air quality in the KRI, specifically in the two largest cities of Erbil and Sulaimani, has deteriorated. The root causes were found to be political instability and wars in the region, a sharp increase in population, and poor public services. Similar to many other cities in the developing countries, sources such as transportation have contributed in the pollution. In addition, other significant sources such as dust storms, large and private power generators as well as household kerosene heaters which might not be present in other countries were found contributing in escalation of the pollution. It is concluded that air pollution in theKRIis the outcome of a variety of causes and sources some of which may not be common in other parts of the world.